1). 18 / √27 ( √ 21•1/3 - √ 6• 3/4 ) + ( - √12/ 2 ) : √0,(3)
2). m( √3 + 2 ) + n( √3 -2 ) = 3√3 - 2 ( determinați m si n )
Răspunsuri la întrebare
Răspuns de
2
m √3 + 2m + √3n - 2n = 3√3 -2
( 2 m -2n ) + ( m +n ) √3 = - 2 + 3√3
daca 2m -2n = -2 / :2 ⇒ m - n = -1
m + n =3 la adunam
-------------------
2m / = 2
m=1 si n =2
( 2 m -2n ) + ( m +n ) √3 = - 2 + 3√3
daca 2m -2n = -2 / :2 ⇒ m - n = -1
m + n =3 la adunam
-------------------
2m / = 2
m=1 si n =2
Alte întrebări interesante
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă